HUMAN SECURITY AND HUMAN RIGHTS IN INDONESIA: HUMAN TRAFFICKING ISSUE IN EAST NUSA TENGGARA - Wandi Abbas (International Journal of Economics Management and Social Science, 2018)
The main focus of the human security concept is understanding the security in the broad dimension that is concerned to socio-economic, health and environmental conditions which threaten the physical security of individual. Human rights, the human basic values, ​​has been regulated in international law. Human trafficking is a basic issue of both concepts. Human trafficking has violated and flattened the values ​​of human security concepts as well as human rights that have become a common precept. On the issue of human trafficking, human security and human rights are phenomena which prove that human existence becomes the main concern of the completion. This paper is a qualitative method, explaining the issue by literature review and interview as well as research refers to various national and international instruments relating to human trafficking. This study argued that in Indonesia, particularly in East Nusa Tenggara, it is vulnerable to human trafficking practices that have an impact on individual insecurity and human rights violations.The rise of human trafficking cases proves that the existence of individual security needs to be considered. East Nusa Tenggara is one of the most vulnerable areas of human trafficking in Indonesia, this mainly due to the economic, educational and other sectors. Financial needs that became the main thing in life in the community became their main cause trapped in the case of human trafficking. In addition, the lack of public understanding about human trafficking is the reason to become victims. The role of the government as an obliging and responsible actor to protect the citizens is not significant, one of which socialization to various regions of human trafficking has not been maximal, which is only done at the government level. Furthermore, the response to the victimized community has not been maximally handling.